Positive electrode film-forming additive and preparation method and application thereof
By using alkylamide alkoxysilane as the positive electrode film forming additive in high-nickel ternary material batteries, the problems of poor structural stability and short cycle life of high-nickel ternary material are solved, and the high-temperature cycle stability of the battery is achieved and Significantly improved security.
Patent Information
- Application Number
- CN202411619976.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
AI Technical Summary
High-nickel ternary materials have poor structural stability and short cycle life.
Using alkylamide alkoxysilane as the positive electrode film forming additive, the compatibility with the positive electrode material is enhanced, the uniform formation of SEI film is promoted, the dissolution of transition metal elements is inhibited, the film forming performance of the electrolyte is improved, and the electrolyte is prevented from decomposition. Improve the structural stability of the positive electrode in other ways.
It significantly improves the battery's high-temperature cycle stability and safety, extends the battery's cycle life, improves the battery's inflation problem, and improves the battery's overall performance.
Smart Images

Figure BDA0005133185420000011 
Figure BDA0005133185420000022 
Figure BDA0005133185420000041
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode film-forming additive, a preparation method and application thereof. Background Art
[0002] With the growing demand for power battery energy density in the new energy vehicle industry, high-nickel ternary power batteries have been widely favored by the market due to their excellent energy density.
[0003] Although high-nickel ternary materials have significant advantages over lithium iron phosphate in terms of energy density, their cycle life performance has not yet reached a completely satisfactory level. This problem is largely due to the poor structural stability of high-nickel ternary materials. 4+ The strong oxidizing property of nickel will cause the electrolyte to decompose on the surface of the material. During the cycle, irreversible phase changes may occur on the surface of the ternary material, as well as the dissolution of transition metal elements. These are the key factors that lead to the capacity decay of the ternary material. The shortcomings of high-nickel ternary materials in terms of cycle life have also aroused widespread concern and worry among consumers. Summary of the invention
[0004] The main purpose of the present invention is to provide a positive electrode film-forming additive, a preparation method and application thereof, so as to solve the problems of poor structural stability and short cycle life of high-nickel ternary materials in the prior art.
[0005] In order to achieve the above object, according to one aspect of the present invention, a positive electrode film-forming additive is provided. The positive electrode film-forming additive is an alkylamide alkoxysilane having a structure shown in the general formula (I):
[0006]
[0007] In the general formula (I), R1, R2 and R3 are independently selected from C1 to C15 straight chain or branched chain alkyl groups; R4 is selected from C3 to C18 straight chain or branched chain alkylene groups. The alkylamide alkoxysilane of the present application is used as a positive electrode film-forming additive to enhance compatibility with positive electrode materials, promote uniform formation of SEI film, inhibit the dissolution of transition metal elements at high temperatures, improve the film-forming performance of the electrolyte on the positive electrode surface, avoid side reactions between the positive electrode interface and the electrolyte, enhance the structural stability of the positive electrode, prevent decomposition of the electrolyte, improve the flatulence problem of the battery, and significantly improve the high temperature cycle stability and safety of the battery.
[0008] Furthermore, in the general formula (I), R1, R2 and R3 are independently selected from C1-C4 straight-chain or branched alkyl groups; and / or, R4 is selected from C3-C6 straight-chain or branched alkylene groups; preferably, R1, R2 and R3 are independently selected from C1-C4 straight-chain alkyl groups; and / or, R4 is selected from C3-C6 straight-chain alkylene groups; more preferably, R1, R2 and R3 are independently selected from methyl, ethyl or propyl groups, and R4 is selected from propylene, butylene or pentylene. Under the above conditions, on the one hand, the synthesis process of alkylamide alkoxysilane is simpler, and on the other hand, the solubility and stability of alkylamide alkoxysilane in the electrolyte when used as a positive electrode film-forming additive can be further improved, which is more conducive to improving the charge and discharge rate of the battery.
[0009] Furthermore, the positive electrode film-forming additive is
[0010] The above-mentioned alkylamide alkoxysilane has a stronger compatibility with the positive electrode material, and the formed CEI film is more flexible and stable. The SEI film is more flexible and elastic at high temperature, and has better stability, which is more conducive to improving the structural stability of the positive electrode material and enhancing the overall performance of the battery.
[0011] According to another aspect of the present invention, a method for preparing the above-mentioned cathode film-forming additive is provided. The raw materials for preparation include alkoxysilane and α-olefin amide, and the α-olefin amide, alkoxysilane and a first solvent are mixed in the presence of a catalyst to obtain the cathode film-forming additive. The preparation method of the present application is simple to operate, easy to mass produce, and the product has high purity.
[0012] Further, the molar ratio of α-olefin amide and alkoxysilane is 1:(8-20); and / or, α-olefin amide includes 3-butene amide and / or acrylamide; and / or, alkoxysilane includes one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane and ethyltripropoxysilane. Under the above conditions, the source of raw materials is wider, the raw materials cooperate with each other, the compatibility is good, the reaction between α-olefin amide and alkoxysilane is more sufficient, the cost is lower, and the CEI film formed by the obtained alkylamide alkoxysilane is more flexible and stable, which is more conducive to solving the problems of poor structural stability and short cycle life of high-nickel ternary materials.
[0013] Further, the catalyst includes one or more of H2PtCl6, (Ph3P)4Pd, (Ph3P)2PdCl2, (PhCN)2PdCl2 and (Ph3P)2NiCl2; and / or, the first solvent includes one or more of ethanol, methanol and acetone; and / or, the mixing also includes the steps of heating reflux and rotary evaporation in sequence, preferably, the heating reflux temperature is 50-70°C, the time is 2-48h; and / or, the rotary evaporation temperature is 40-50°C, the pressure is 0.1-1MPa, and the time is 0.5-1h. Under the above conditions, the yield and purity of the product can be more effectively improved, and the occurrence of side reactions can be reduced.
[0014] According to another aspect of the present invention, an electrolyte is provided, comprising the above-mentioned positive electrode film-forming additive, a lithium salt and a second solvent. The above-mentioned electrolyte can significantly improve the cycle stability and safety of the battery while maintaining good conductivity.
[0015] Further, the lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalate)phosphate and lithium tetrafluoro(oxalate)phosphate; and / or, the second solvent includes ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate , ethyl propionate, ethyl methyl carbonate, propyl ether, butyl ether, glutaronitrile, cyclopentane sulfone, methyl propionate, ethyl propionate, butyl propionate and ethyl butyrate; and / or, by weight percentage, the positive electrode film-forming additive accounts for 0.5-9% of the electrolyte, preferably 0.5-2%; and / or, the lithium salt accounts for 8-16% of the electrolyte, preferably 9-14%; and / or, the second solvent accounts for 78-90% of the electrolyte, preferably 85-90%. Under the above conditions, the specific content and type of positive electrode film-forming additives and lithium salts cooperate with each other to optimize the CEI film, so that it can more effectively prevent side reactions without excessively hindering the transmission of lithium ions, thereby further improving the stability of the battery and extending its life while maintaining a high energy density and power density.
[0016] According to another aspect of the present invention, a battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises the above-mentioned positive electrode film-forming additive. The battery of the present application adopts the above-mentioned positive electrode film-forming additive of a specific structure, which effectively prevents the decomposition of the electrolyte, thereby being able to solve the flatulence problem of the battery. The battery of the present application has good cycle stability and safety, high energy density and power output, and is suitable for various portable electronic devices, electric vehicles and large-scale energy storage systems.
[0017] Furthermore, the positive electrode material includes a nickel-containing positive electrode material, and the nickel-containing positive electrode material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium nickel cobalt ferrite oxide, and lithium nickel cobalt magnesium oxide. The positive electrode film-forming additive of the present application is more compatible with the above materials, and can preferentially form a more flexible and stable CEI film on the surface of the above materials, which can more effectively inhibit the dissolution of transition metal elements in the above positive electrode materials, reduce the irreversible phase change on the surface of the material, and thus be more conducive to improving the structural stability and cycle life of the positive electrode materials.
[0018] The positive electrode film-forming additive of the present invention is an alkylamide alkoxysilane with a specific structure. The nitrogen atom containing a lone electron pair in the amide structure is easy to lose electrons, showing a lower oxidation potential, and can preferentially form a CEI film on the surface of the high-nickel ternary positive electrode; the high bond energy characteristics of the Si-O bond and the chain alkyl (CH2) n The flexible characteristics make the formed CEI film more flexible and stable. Furthermore, the SEI film is more flexible and elastic at high temperatures and has better stability.
[0019] Using the alkylamide alkoxysilane of the present invention as a positive electrode film-forming additive can inhibit the dissolution of transition metal elements at high temperatures, improve the film-forming performance of the electrolyte on the positive electrode surface, avoid side reactions between the positive electrode interface and the electrolyte, enhance the structural stability of the positive electrode, prevent the decomposition of the electrolyte, improve the flatulence problem of the battery, and significantly improve the high-temperature cycle stability and safety of the battery. DETAILED DESCRIPTION
[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0021] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the numbers used in this way can be interchanged under appropriate circumstances to describe the embodiments of the present invention.
[0022] As described in the background of the present invention, the prior art has the problems of poor structural stability and short cycle life of high-nickel ternary materials. In order to solve the above problems, in a typical embodiment of the present invention, a positive electrode film-forming additive is provided, and the positive electrode film-forming additive is an alkylamide alkoxysilane having a structure shown in general formula (I):
[0023]
[0024] In the general formula (I), R1, R2 and R3 are independently selected from C1-C15 straight chain or branched chain alkyl groups; R4 is selected from C3-C18 straight chain or branched chain alkylene groups.
[0025] The positive electrode film-forming additive of the present application is an alkylamide alkoxysilane with a specific structure. The nitrogen atom containing a lone electron pair in the amide structure is easy to lose electrons, showing a lower oxidation potential, and can preferentially form a CEI film on the surface of the high-nickel ternary positive electrode; the high bond energy characteristics of the Si-O bond and the chain alkyl (CH2) n The flexible characteristics make the formed CEI film flexible and stable. Furthermore, the SEI film is more flexible and elastic at high temperatures and has better stability.
[0026] Using the alkylamide alkoxysilane of the present application as a positive electrode film-forming additive can enhance the compatibility with the positive electrode material, promote the uniform formation of the SEI film, inhibit the dissolution of transition metal elements at high temperature, improve the film-forming performance of the electrolyte on the positive electrode surface, avoid side reactions between the positive electrode interface and the electrolyte, enhance the structural stability of the positive electrode, prevent the decomposition of the electrolyte, improve the flatulence problem of the battery, and significantly improve the high-temperature cycle stability and safety of the battery.
[0027] In order to further improve the solubility and reactivity of the positive electrode film-forming additive, the inventors have optimized the length and type of the alkyl group and the alkylene group through a large number of experiments. In a preferred embodiment, in the general formula (I), R1, R2 and R3 are independently selected from C1 to C4 straight chain or branched alkyl groups; and / or, R4 is selected from C3 to C6 straight chain or branched alkylene groups; preferably, R1, R2 and R3 are independently selected from C1 to C4 straight chain alkyl groups; and / or, R4 is selected from C3 to C6 straight chain alkylene groups; more preferably, R1, R2 and R3 are independently selected from methyl, ethyl or propyl groups, and R4 is selected from propylene, butylene or pentylene. Under the above conditions, on the one hand, the synthesis process of alkylamide alkoxysilane is simpler, and on the other hand, it can further improve the solubility and stability of alkylamide alkoxysilane in the electrolyte when used as a positive electrode film-forming additive, which is more conducive to improving the charge and discharge rate of the battery.
[0028] After a lot of experimental research, the inventors have selected the alkylamide alkoxysilane type with a specific structure. In a preferred embodiment, the positive electrode film-forming additive is
[0029] The above-mentioned alkylamide alkoxysilane has a stronger compatibility with the positive electrode material, and the formed CEI film is more flexible and stable. The SEI film is more flexible and elastic at high temperature, and has better stability, which is more conducive to improving the structural stability of the positive electrode material and enhancing the overall performance of the battery.
[0030] In another typical embodiment of the present invention, a method for preparing the above-mentioned positive electrode film-forming additive is also provided, wherein the raw materials include alkoxysilane and α-olefin amide, and the α-olefin amide, alkoxysilane and the first solvent are mixed in the presence of a catalyst to obtain the positive electrode film-forming additive. The preparation method of the present application is simple to operate, easy to mass produce, and the product has high purity.
[0031] In a preferred embodiment, the molar ratio of α-olefin amide and alkoxysilane is 1:(8-20); and / or, α-olefin amide includes 3-butene amide and / or acrylamide; and / or, alkoxysilane includes one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane and ethyltripropoxysilane. Under the above conditions, the source of raw materials is wider, the raw materials cooperate with each other, the compatibility is good, the reaction between α-olefin amide and alkoxysilane is more sufficient, the cost is lower, and the CEI film formed by the obtained alkylamide alkoxysilane is more flexible and stable, which is more conducive to solving the problems of poor structural stability and short cycle life of high nickel ternary materials.
[0032] In a preferred embodiment, the catalyst includes one or more of H2PtCl6, (Ph3P)4Pd, (Ph3P)2PdCl2, (PhCN)2PdCl2 and (Ph3P)2NiCl2; and / or, the first solvent includes one or more of ethanol, methanol and acetone; and / or, the mixing further includes the steps of heating reflux and rotary evaporation in sequence, preferably, the heating reflux temperature is 50-70°C, the time is 2-48h; and / or, the rotary evaporation temperature is 40-50°C, the pressure is 0.1-1MPa, and the time is 0.5-1h. Under the above conditions, the yield and purity of the product can be more effectively improved, and the occurrence of side reactions can be reduced.
[0033] In another typical embodiment of the present invention, an electrolyte is also provided, comprising the above-mentioned positive electrode film-forming additive, a lithium salt and a second solvent. As mentioned above, the positive electrode film-forming additive of the present application can preferentially form a flexible and stable CEI film on the surface of the high-nickel ternary positive electrode, the film-forming performance of the electrolyte on the positive electrode surface is improved, and the side reaction between the electrolyte and the positive electrode interface is effectively suppressed, effectively preventing the decomposition of the electrolyte. The electrolyte of the present application can significantly improve the cycle stability and safety of the battery while maintaining good conductivity.
[0034] Regarding the lithium salt and the second solvent, conventional types in the art can be used. In a preferred embodiment, the lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium trifluoromethylsulfonate, bis(pentafluoroethylsulfonyl imide) lithium, bis(trifluoromethylsulfonyl imide) lithium, bis(fluorosulfonyl imide) lithium, difluoro(bisoxalate) lithium phosphate and tetrafluoro(oxalate) lithium phosphate; and / or, the second solvent includes one or more of organic carbonate, ionic liquid, polyether, aromatic ether, C1-C30 alkyl ether, cyclic ether, carboxylate, sulfone, nitrile and dinitrile, preferably ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl propionate, ethyl methyl carbonate, propyl ether, butyl ether, glutaronitrile, cyclopentane sulfone, methyl propionate, ethyl propionate, butyl propionate and ethyl butyrate, more preferably ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate. The above-mentioned types of lithium salts and second solvents are compatible with alkylamide alkoxysilanes and lithium salts, and can cooperate with each other to effectively reduce the occurrence of side reactions, thereby inhibiting the performance degradation caused by the decomposition of the electrolyte.
[0035] With respect to the electrolyte including the novel positive electrode film-forming additive of the present application, the inventor has optimized its composition. In a preferred embodiment, the positive electrode film-forming additive accounts for 0.5-9% of the electrolyte, preferably 0.5-2% by weight; and / or the lithium salt accounts for 8-16% of the electrolyte, preferably 9-14%; and / or the second solvent accounts for 78-90% of the electrolyte, preferably 85-90%. If the content of the positive electrode film-forming additive is too much, an excessively thick interface film may be formed on the positive electrode surface, increasing the resistance of lithium ions passing through the interface, affecting the capacity and rate performance of the battery, and increasing the cost of the electrolyte and the raw materials of the battery. If the content of the positive electrode film-forming additive is too little, the positive electrode surface protective film may be unstable, so that the positive electrode material and the electrolyte are in direct contact, affecting the safety and cycle performance of the battery. Under the above conditions, specific contents of positive electrode film-forming additives and lithium salts work together to optimize the CEI membrane, so that it can more effectively prevent side reactions without excessively hindering the transmission of lithium ions, thereby further improving battery stability and extending battery life while maintaining a high energy density and power density.
[0036] In order to further improve the dissolution effect of lithium salt and reduce the side reaction between lithium salt and additives, the inventors specifically limit the preparation method of the electrolyte, especially the order of adding each raw material. In another typical embodiment of the present invention, a method for preparing the above-mentioned electrolyte is also provided, comprising the following steps: mixing the lithium salt and the second solvent, and then adding the positive electrode film-forming additive to obtain an electrolyte. The preparation method is simple and fast, avoids complex post-processing processes, is conducive to reducing production costs, improving production efficiency, and is suitable for large-scale industrial production.
[0037] In another typical embodiment of the present invention, a battery is also provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises the above-mentioned positive electrode film-forming additive. The battery of the present application adopts the above-mentioned positive electrode film-forming additive with a specific structure, which effectively prevents the decomposition of the electrolyte, thereby solving the problem of battery flatulence. The battery of the present application has good cycle stability and safety, high energy density and power output, and is suitable for various portable electronic devices, electric vehicles and large-scale energy storage systems.
[0038] In a preferred embodiment, the positive electrode material includes a nickel-containing positive electrode material, and the nickel-containing positive electrode material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium nickel cobalt ferrite oxide, and lithium nickel cobalt magnesium oxide. The positive electrode film-forming additive of the present application is more compatible with the above materials, and can preferentially form a more flexible and stable CEI film on the surface of the above materials, which can more effectively inhibit the dissolution of transition metal elements in the above positive electrode materials, reduce the irreversible phase change on the surface of the material, and thus help to improve the structural stability and cycle life of the positive electrode materials.
[0039] In a preferred embodiment, the nickel-containing positive electrode material further comprises a cathode active material, wherein the cathode active material comprises one or more of acetylene black, LiCoO2, LiNiMnCoO2, LiNiCoAlO2, LiFePO4 and LiNiMnO2; and / or, the negative electrode material comprises Li4Ti5O 12 , LiFePO4, artificial graphite, natural graphite, silicon material, silicon-carbon material, silicon-carbon-graphite composite material and silicon-carbon-silicon oxide composite material; and / or, the battery also includes a diaphragm, the material of the diaphragm includes one or more of polyimide, polyethylene, polypropylene and polyethylene terephthalate; preferably polyethylene and polypropylene. The above-mentioned types of materials can cooperate with the specific types of positive electrode film-forming additives of the present application to further improve the energy density, cycle stability, safety, charge and discharge rate and environmental adaptability of the battery, thereby more effectively improving the overall performance of the battery.
[0040] By optimizing the positive electrode, negative electrode and diaphragm materials and combining the electrolyte with the above-mentioned specific composition and structure, the battery of the present application significantly improves the cycle stability and safety while maintaining high energy density, especially under extreme temperature and high power output conditions, and shows excellent performance, providing more reliable and efficient energy solutions for portable electronic devices, electric vehicles and large-scale energy storage systems. In addition, the battery design also takes environmental protection and economy into consideration, using recyclable materials and low-cost production technology, and has contributed to the development of sustainable energy technology.
[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0042] Example 1
[0043] Preparation of positive electrode film-forming additives:
[0044] In the presence of catalyst H2PtCl6, 3-buteneamide and methyltriethoxysilane (the molar ratio of the two is 1:8) are mixed evenly in acetone, and refluxed in a closed condition at 60°C to react for 12 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 45°C and 0.5MPa for 1 hour to remove acetone and unreacted raw material methyltriethoxysilane to obtain a positive electrode film-forming additive, which is used as a positive electrode film-forming additive.
[0045] Specifically, the reaction equation of 3-buteneamide and methyltriethoxysilane is as follows:
[0046]
[0047] Preparation of electrolyte:
[0048] Calculated by weight percentage, the components of the electrolyte include: 86% solvent (ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 3:3:4), 12% lithium salt (lithium hexafluorophosphate), and 2% positive electrode film-forming additive.
[0049] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), the solvents were mixed evenly, and lithium salt was slowly added. After the lithium salt was completely dissolved, a positive electrode film-forming additive was added, and the mixture was stirred evenly to obtain an electrolyte.
[0050] Preparation of positive electrode materials:
[0051] A solid substance (in terms of weight percentage, comprising 97% of nickel-containing positive electrode material NCM811 (i.e., the molar ratio of Ni, Co, and Mn is 8:1:1), 1.5% of cathode active material acetylene black, and 1.5% of binder PVDF) and N-methylpyrrolidone are mixed to form a slurry, which is then coated on a 12-micron thick aluminum foil, dried, and rolled to obtain a positive electrode sheet comprising the positive electrode material.
[0052] Preparation of negative electrode materials:
[0053] A solid substance (by weight percentage, including 95% artificial graphite, 2% anode active material acetylene black, and 3% binder styrene-butadiene rubber) is mixed with deionized water to form a slurry, which is then coated on an 8-micron thick copper foil, dried, and rolled to obtain a negative electrode sheet including a negative electrode material.
[0054] Preparation of the battery:
[0055] In a dry environment with a leakage point ≤-50℃, stack the positive electrode sheet, diaphragm (model: 9233), and negative electrode sheet in sequence to ensure that the diaphragm completely separates the positive electrode sheets and the negative electrode completely covers the positive electrode. The sheets are stacked to form a battery cell, and the electrodes are encapsulated in an aluminum-plastic film of a fixed size using glue-attached tabs to form a soft-pack battery to be filled with liquid. Subsequently, the electrolyte is injected into the soft-pack battery, sealed, formed, aged, and sealed to obtain a battery.
[0056] Example 2
[0057] The only difference from Example 1 is:
[0058] Preparation of positive electrode film-forming additives:
[0059] In the presence of catalyst H2PtCl6, acrylamide and methyltrimethoxysilane (the molar ratio of the two is 1:15) are mixed evenly in acetone, and refluxed under closed conditions at 75°C to react for 8 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 45°C and 0.5MPa for 1 hour to remove acetone and unreacted raw material methyltrimethoxysilane to obtain alkylamide alkoxysilane, which is used as a positive electrode film-forming additive. Specifically, the reaction equation of acrylamide and methyltrimethoxysilane is as follows:
[0060]
[0061] Preparation of electrolyte:
[0062] Calculated by weight percentage, the components of the electrolyte include: 87% solvent (ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 3:3:4), 12% lithium salt (lithium hexafluorophosphate), and 1% positive electrode film-forming additive.
[0063] Example 3
[0064] The only difference from Example 1 is:
[0065] Preparation of positive electrode film-forming additives:
[0066] In the presence of a catalyst, 3-buteneamide and ethyltripropoxysilane (the molar ratio of the two is 1:10) are mixed evenly in acetone, and refluxed under closed conditions at 85°C to react for 18 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 45°C and 0.5MPa for 1 hour to remove acetone and unreacted raw material ethyltripropoxysilane to obtain alkylamide alkoxysilane, which is used as a positive electrode film-forming additive. Specifically, the reaction equation of 3-buteneamide and ethyltripropoxysilane is as follows:
[0067]
[0068] Preparation of electrolyte:
[0069] Calculated by weight percentage, the components of the electrolyte include: 87.5% solvent (ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 3:3:4), 12% lithium salt (lithium hexafluorophosphate), and 0.5% positive electrode film-forming additive.
[0070] Example 4
[0071] The only difference from Example 1 is:
[0072] Preparation of positive electrode film-forming additives:
[0073] In the presence of catalyst H2PtCl6, acrylamide and ethyltriethoxysilane (the molar ratio of the two is 1:20) are mixed evenly in acetone, and refluxed under closed conditions at 90°C to react for 20 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 45°C and 0.5MPa for 1 hour to remove acetone and unreacted raw material ethyltriethoxysilane to obtain alkylamide alkoxysilane, which is used as a positive electrode film-forming additive. Specifically, the reaction equation of acrylamide and ethyltriethoxysilane is as follows:
[0074]
[0075] Preparation of electrolyte:
[0076] Calculated by weight percentage, the components of the electrolyte include: 86.5% solvent (ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 3:3:4), 12% lithium salt (lithium hexafluorophosphate), and 1.5% positive electrode film-forming additive.
[0077] Example 5
[0078] The only difference from Example 1 is:
[0079] Preparation of positive electrode film-forming additives:
[0080] In the presence of (Ph3P)4Pd catalyst, 3-buteneamide and methyltriethoxysilane (the molar ratio of the two is 1:8) are mixed evenly in methanol and refluxed in a closed condition at 50°C to react for 48 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 50°C and 0.1MPa for 1 hour to remove acetone and unreacted raw material methyltriethoxysilane to obtain alkylamide alkoxysilane, which is used as a positive electrode film-forming additive.
[0081] Example 6
[0082] The only difference from Example 1 is:
[0083] Preparation of positive electrode film-forming additives:
[0084] In the presence of (Ph3P)2NiCl2 catalyst, 3-buteneamide and methyltriethoxysilane (the molar ratio of the two is 1:20) are mixed evenly in ethanol and refluxed under closed conditions at 70°C to react for 2 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 1MPa for 0.5 hours to remove acetone and unreacted raw material methyltriethoxysilane to obtain alkylamide alkoxysilane, which is used as a positive electrode film-forming additive.
[0085] Example 7
[0086] The only difference from Example 1 is:
[0087] Preparation of electrolyte:
[0088] Calculated by weight percentage, the components of the electrolyte include: 90% solvent, 9% lithium salt, and 1% positive electrode film-forming additive.
[0089] Example 8
[0090] The only difference from Example 1 is:
[0091] Preparation of electrolyte:
[0092] Calculated by weight percentage, the components of the electrolyte include: 85% solvent, 14% lithium salt, and 1% positive electrode film-forming additive.
[0093] Example 9
[0094] The only difference from Example 1 is:
[0095] Preparation of electrolyte:
[0096] Calculated by weight percentage, the components of the electrolyte include: 90% solvent, 9.5% lithium salt, and 0.5% positive electrode film-forming additive.
[0097] Example 10
[0098] The only difference from Example 1 is:
[0099] Preparation of electrolyte:
[0100] Calculated by weight percentage, the components of the electrolyte include: 78% solvent, 13% lithium salt, and 9% positive electrode film-forming additive.
[0101] Embodiment 11
[0102] The only difference from Example 1 is:
[0103] The nickel-containing positive electrode material is lithium nickel cobalt aluminum oxide, and the diaphragm material is polyethylene.
[0104] Example 12
[0105] The only difference from Example 1 is:
[0106] The nickel-containing positive electrode material is lithium nickel manganese oxide, and the diaphragm material is polyimide.
[0107] Comparative Example 1
[0108] The only difference from Example 1 is:
[0109] Calculated by weight percentage, the components of the electrolyte include: 87.2% of solvent, 12% of lithium salt (lithium hexafluorophosphate), 0.8% of positive electrode film-forming additive (LiODFB, lithium difluorooxalatoborate), and excluding alkylamide alkoxysilane.
[0110] Comparative Example 2
[0111] The only difference from Example 1 is:
[0112] In the electrolyte, the positive electrode film-forming additive uses TMSP (tri(trimethylsilyl) phosphate) instead of alkylamide alkoxysilane.
[0113] Comparative Example 3
[0114] The only difference from Example 1 is:
[0115] Calculated by weight percentage, the components of the electrolyte include: 87% solvent, 12% lithium salt (lithium hexafluorophosphate), 1% positive electrode film-forming additive (PS, polystyrene), and excluding alkylamide alkoxysilane.
[0116] Comparative Example 4
[0117] The only difference from Example 1 is:
[0118] Calculated by weight percentage, the components of the electrolyte include: 88% solvent, 12% lithium salt (lithium hexafluorophosphate), and excluding positive electrode film-forming additives (alkylamide alkoxysilane).
[0119] The electrical performance test results of the batteries prepared in the above examples and comparative examples are shown in Table 1.
[0120] Test method:
[0121] Electrical performance test: The battery is formed and divided into different capacities using a battery test cabinet, wherein the formation process is 0.02C constant current charging to 3.0V, and 0.1C constant current charging to 3.7V; the aging process is 45℃ for 12 hours; the division process is 0.33C constant current and constant voltage charging to 4.25V, the cut-off current is 0.05C, and 0.33C constant current discharge to 2.8V, repeated 3 times. Then the battery is charged and discharged at a high temperature of 55℃ with 1C / 1C constant current and constant voltage for 500 cycles, and the voltage range is set to 2.8~4.25V. After the cycle is completed, the impedance of the battery is tested with an internal resistance meter, and the thickness of the battery is tested with a vernier caliper. The internal resistance growth rate is equal to the difference before and after the cycle divided by the internal resistance of the battery before the cycle, and the thickness growth rate is equal to the difference before and after the cycle divided by the thickness of the battery before the cycle.
[0122] Table 1
[0123]
[0124]
[0125] As can be seen from the above, compared with the comparative example, the positive electrode film-forming additives in the embodiments of the present invention are alkylamide alkoxysilanes with a specific structure. The nitrogen atom containing a lone electron pair in the amide structure is easy to lose electrons, showing a lower oxidation potential, and can preferentially form a CEI film on the surface of the high-nickel ternary positive electrode; the high bond energy characteristics of the Si-O bond and the chain alkyl (CH2) n The flexible characteristics make the formed CEI film flexible and stable. Furthermore, the SEI film is more flexible and elastic at high temperatures, and has better stability. By adding specific types of positive electrode film-forming additives, the first charge and discharge coulomb efficiency of the electrolyte and the high temperature 55°C capacity retention rate in the soft pack battery cycle test have been significantly improved, the internal resistance and battery thickness have been significantly reduced, the positive electrode stability has been improved, the decomposition of the electrolyte has been effectively prevented, the battery's flatulence problem has been improved, and the high temperature cycle performance of the high nickel ternary lithium battery has been greatly improved.
[0126] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the electrochemical performance of the battery is even better.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode film-forming additive, characterized in that: The positive electrode film-forming additive is an alkylamide alkoxysilane having a structure shown in general formula (I): In the general formula (I), R1, R2 and R3 are independently selected from C1 to C15 straight or branched alkyl groups; R4 is selected from C3-C18 straight chain or branched chain alkylene.
2. The positive electrode film-forming additive according to claim 1, characterized in that: In the general formula (I), R1, R2 and R3 are independently selected from C1-C4 straight chain or branched chain alkyl groups; and / or, R4 is selected from a C3-C6 straight or branched alkylene group; Preferably, R1, R2 and R3 are independently selected from C1-C4 straight-chain alkyl groups; and / or, R4 is selected from C3-C6 straight-chain alkylene groups; More preferably, R1, R2 and R3 are independently selected from methyl, ethyl or propyl, and R4 is selected from propylene, butylene or pentylene.
3. The positive electrode film-forming additive according to claim 1 or 2, characterized in that: The positive electrode film-forming additive is One or more of .
4. The method for preparing the positive electrode film-forming additive according to any one of claims 1 to 3, characterized in that: The preparation raw materials include alkoxysilane and α-olefin amide, The α-olefin amide, the alkoxysilane and the first solvent are mixed in the presence of a catalyst to obtain the positive electrode film-forming additive.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the α-olefin amide to the alkoxysilane is 1:(8-20); and / or, The α-olefin amide includes 3-butene amide and / or acrylamide; and / or, The alkoxysilane includes one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane and ethyltripropoxysilane.
6. The preparation method according to claim 4 or 5, characterized in that: The catalyst comprises one or more of H2PtCl6, (Ph3P)4Pd, (Ph3P)2PdCl2, (PhCN)2PdCl2 and (Ph3P)2NiCl2; and / or, The first solvent comprises one or more of ethanol, methanol and acetone; and / or, The mixing further comprises the steps of heating reflux and rotary evaporation performed sequentially. Preferably, the heating reflux temperature is 50-70°C and the time is 2-48h; and / or the rotary evaporation temperature is 40-50°C, the pressure is 0.1-1MPa and the time is 0.5-1h.
7. An electrolyte, characterized in that: The method comprises the positive electrode film-forming additive according to any one of claims 1 to 3, a lithium salt and a second solvent.
8. The electrolyte according to claim 7, characterized in that The lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalato)phosphate and lithium tetrafluoro(oxalato)phosphate; and / or, The second solvent comprises one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl propionate, ethyl methyl carbonate, propyl ether, butyl ether, glutaronitrile, sulfolane, methyl propionate, ethyl propionate, butyl propionate and ethyl butyrate; and / or, Calculated by weight percentage, The positive electrode film-forming additive accounts for 0.5-9% of the electrolyte, preferably 0.5-2%; and / or, The lithium salt accounts for 8-16% of the electrolyte, preferably 9-14%; and / or, The second solvent accounts for 78-90% of the electrolyte, preferably 85-90%.
9. A battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The electrolyte comprises the positive electrode film-forming additive according to any one of claims 1 to 3.
10. The battery according to claim 9, characterized in that The material of the positive electrode includes a nickel-containing positive electrode material, and the nickel-containing positive electrode material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium nickel cobalt ferrite oxide and lithium nickel cobalt magnesium oxide.
Citation Information
Cited By
Gel electrolyte, gel-state battery and preparation method
CN121922711A